2009
DOI: 10.1007/s10533-009-9296-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of organic matter in a freshwater estuarine sediment: long-term degradation experiments with and without nitrate supply

Abstract: Organic carbon degradation experiments were carried out using flow-through reactors with sediments collected from an intertidal freshwater marsh of an eutrophic estuary (The Scheldt, Belgium). Concentrations of nitrate, nitrite, dissolved inorganic carbon (DIC), dissolved organic carbon, methane, dissolved cations (Ca 2? , Mg 2? , Na ? and K ? ), total dissolved Fe, phosphate and alkalinity were measured in the outflow solutions from reactors that were supplied with or without the terminal electron acceptor ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
2
12
0
3
Order By: Relevance
“…Using flow-through reactors and intertidal marsh sediments, Pallud et al (2007) found that nitrate reduction led to faster rates of organic matter decomposition versus sulfate reduction. In another study, supplying nitrate also led to greater mineralization than in control treatments with no terminal electron acceptor additions (Abell et al, 2009); the authors suggest that this increase occurred because denitrifiers were able to access soil organic carbon that was not available to the fermenting microbial community. The results of our field transplant experiments were also equivocal, but overall they support the hypothesis that the dominant TEA pathway can influence carbon mineralization rates.…”
Section: Role Of Electron Acceptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Using flow-through reactors and intertidal marsh sediments, Pallud et al (2007) found that nitrate reduction led to faster rates of organic matter decomposition versus sulfate reduction. In another study, supplying nitrate also led to greater mineralization than in control treatments with no terminal electron acceptor additions (Abell et al, 2009); the authors suggest that this increase occurred because denitrifiers were able to access soil organic carbon that was not available to the fermenting microbial community. The results of our field transplant experiments were also equivocal, but overall they support the hypothesis that the dominant TEA pathway can influence carbon mineralization rates.…”
Section: Role Of Electron Acceptorsmentioning
confidence: 95%
“…Among studies that have manipulated the TEA pathway through substrate amendments, some report greater rates of carbon mineralization in the presence of NO 3 À compared to methanogenesis (Pallud et al, 2007;Abell et al, 2009) or SO 4 2À compared to methanogenesis (Reddy and Graetz, 1988;Weston et al, 2006;Pallud et al, 2007). However, in a comparison of 10 different wetland soils, D'Angelo and Reddy (1999) did not observe a difference in organic carbon mineralization rates under denitrifying, sulfate-reducing or methanogenic conditions.…”
Section: Introductionmentioning
confidence: 94%
“…25 A fermentação é uma das vias mais eficientes de transformação microbiológica da matéria orgânica aquática sedimentar, fornecendo substrato para os subsequentes processos anóxicos, responsáveis pela etapa final de degradação do carbono orgânico. 26 Esta decomposição anaeróbia dos compostos orgânicos em sedimentos, a qual utiliza em menor escala os óxi-hidróxidos de ferro e manganês, e principalmente os sulfatos como receptores de elétrons, é acompanhada de um aumento na alcalinidade com a produção de HCO 3 -, HS -, HPO 4 2-, FeS 2 , N-amoniacal e precipitação de CaCO 3 , principalmente sob a forma de aragonita e calcita gerados biogenicamente. O CO 2 produzido nesta decomposição é o precursor do ânion bicarbonato, principal responsável pela alcalinidade.…”
Section: A Importância Da Mineralização Da Matéria Orgânica Na Produçunclassified
“…28,29 A oxidação por nitratos é mais efetiva com respeito à matéria orgânica mais lábil, localizada na superfície dos sedimentos de fundo, fornecendo alcalinidade pela formação de CO 2 , além de N 2 e água. 26 Devido à natureza destes últi-mos compostos e das características da degradação anaeróbia, esses processos terminais são mais lentos do que os primeiros. 29 Após o consumo total destes receptores de elétrons, verifica-se a mineralização estritamente anaeróbia da matéria orgânica via metanogênese, nas regiões mais profundas da matriz.…”
Section: A Importância Da Mineralização Da Matéria Orgânica Na Produçunclassified
See 1 more Smart Citation